Peculiarities of the blood system of animals under the conditions of consumption of drinking water containing chlorates - T.E. Kravchun; L.A. Tomashevskaya; L.A. Tomashevskaya; V.A. Prokopov; T.V. Kulish; V.S. Tsytsyruk (Medičnì Perspektivi, 2024)
In modern conditions, providing the population with high-quality drinking water is becoming an increasingly urgent hygienic, scientific, technical, and social problem. Chlorine dioxide can be an alternative reagent for disinfecting drinking water. However, as with chlorine, dangerous by-products, particularly chlorites and chlorates are formed. The processes of development of morphofunctional changes in homeostasis remain insufficiently studied in this aspect. The objective is to determine the nature and peculiarities of changes in hematological indicators in the blood of animals due to the chronic impact of various concentrations of chlorates in drinking water to establish criteria for the hygienic assessment of their adverse effects on the body. The test animals were given drinking water with different concentrations of chlorates daily for 6 months: group 1 – control, group 2 – chlorates at a dose of 0.2 mg/dm³, group 3 – chlorates at a dose of 0.7 mg/dm³, and group 4 – chlorates at a dose of 1.2 mg/dm³. Evaluating the results of experimental studies, it should be noted that the most pronounced changes are observed in groups of animals that received chlorates in concentrations of 0.7 and 1.2 mg/dm³: a gradual decrease in the absolute number of leukocytes, the absolute and relative number of lymphocytes, relative to the indicators of the control group can be observed. In groups of animals that received chlorates in concentrations of 0.7 and 1.2 mg/dm³, a decrease in the absolute number of erythrocytes was observed during the 90 days of the experiment. It was established that the severity of the effects depended on the dose of chlorates and the time of exposure. Thus, the nature and features of changes in hematological indicators in the body of experimental animals during a chronic sanitary-toxicological experiment under the influence of chlorates in drinking water may indicate that chlorates affect the indicators of the blood system, being the indirect signs of disorders of other functional systems in the body, namely – slowing of redox reactions, hypoxic manifestations, reduction and weakening of the immune response and reactivity, etc.